Leadership for Disaster Resilience: Lessons from India - Jacquleen Joseph; Suchita Awasthi; Zubin R. Mulla (Routledge India, 2023)
This book comprehensively conceptualises disaster resilience leadership within the macro context of a risk society. Leadership for disaster resilience has gained prominence in the face of global environmental change, and the need for collaboration, integration, and synergy in addressing this crisis is starker than ever. Drawing on case studies from across India, the volume focuses on leaderships of individuals, bureaucratic and political actors, civil society actors, and institutions. It looks at the ways in which disaster resilience leadership can address key challenges through the application of such theoretical perspectives as integrative public leadership, critical new institutionalism, and comparative realisation focused approaches to social justice. It highlights current leadership practices and envisages sustainable solutions to the environmental crisis by emphasising the need for disaster resilience leadership that could bring about systemic and socio-structural change. Presenting fresh perspectives on leadership research, the book will be an essential read for scholars and researchers of disaster management, social work, management studies, development studies, environmental studies, and public policy. It will also be useful for NGOs and professionals working in the public sector and with civil society bodies. The Open Access version of this book, available at www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives 4.0 license.
Keywords: 360; Social impact of disasters; Management: leadership and motivation; Society and culture: general